Sierra Leone : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2005)
This Joint Staff Advisory Note reviews the Poverty Reduction Strategy Paper (PRSP) for Sierra Leone. The Poverty Reduction Strategy (PRS) provides an adequate framework for reducing poverty in Sierra Leone. The PRSP is the result of an extensive participatory process. The foundation of the PRSP is a series of extensive consultations conducted throughout the country. The IMF staff believes that statistical capacity-building, with donor support, will be essential for monitoring progress in the implementation of the PRSP in Sierra Leone.